Anew Conjugate Gradient Algorithm Based on The (Dai-Liao) Conjugate Gradient Method - SHAHER QAHTAN HUSSEIN; GHASSAN EZZULDDIN ARIF; YOKSAL ABDLL SATTAR (Tikrit Journal of Pure Science, 2020)
In this paper we can derive a new search direction of conjugating gradient method associated with (Dai-Liao method ) the new algorithm becomes converged by assuming some hypothesis. We are also able to prove the Descent property for the new method, numerical results showed for the proposed method is effective comparing with the (FR, HS and DY) methods.